Seismic behavior of precast hollow pier with shallow socket connection - Guoyong Yue; Yunhui Chen; Hu Feng; Liusheng Chu; Xiangming Liu; Xiuling Li; Guosen Zhou; Yinhui Wang (Case Studies in Construction Materials)
Accelerating bridge construction has the potential to alleviate traffic congestion and reduce environmental impact, thus proving to be an efficient construction method. This study proposes the precast hollow concrete pier with shallow socket connection (PHCSS pier) to facilitate easier transportation and assembly. This PHCSS pier comprises a hollow column and a shallow socket foundation. Notably, the column is manufactured using centrifugal casting, and the hollow column is filled with high-strength self-compacting micro-expansive grouting material (GM) up to a designated height. This study investigated the PHCSS pier under varying GM heights through pseudo-static testing. The findings indicated that this connection could effectively transfer loads and meet design criteria. Like the cast-in-place pier (CIP pier), the PHCSS pier exhibited intense plastic deformation and bearing capacity, with a plastic hinge bending failure mode. A larger GM height increased the pier's carrying and energy dissipation capacities but reduced its deformation capacity. The established finite element model was in good agreement with the experiment. When the GM height reached 0.5D, the GM fully exerted the bearing capacity, so 0.5D could be recommended as the critical GM height. At last, this study proposed a bending capacity formula for the socket hollow pier, demonstrating a strong correlation with the experimental findings.